REPRESENTASI FEMINISME DALAM NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN (KAJIAN SEMIOTIKA ROLAND BARTHES) - Rinawati Utari Rifai; Idawati Idawati; Faisal Faisal (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Representation of Feminism in the Novel Cantik Itu Luka by Eka Kurniawan (Roland Barthes's Semiotic Study). This research uses a qualitative descriptive method and aims to describe the meaning of denotation and connotation and the form of representation of feminism contained in the novel. The results of the study show that in general the meaning of denotation reveals the existence of Dewi Ayu and also other figures who live in the city of Halimunda which are very threatened as women because their existence is often underestimated. Meanwhile, the connotative meaning reveals the issue of gender treatment. In addition, the form of representation of feminism contained in the novel is shown by the behavior of men who often see women as beautiful image objects covered in sexual prowess. There are many loss events experienced by female characters in novels such as violence, subordination, marginalization, and sexual objectification.